Response to Merz - Al, Pepijn; Brehaut, Jamie; Weijer, Charles (Current controlled trials in cardiovascular medicine, 2023)
Jon Merz raises two objections to our article on the ethics of behavioral influences in trial recruitment. In this response, we defend our article against these objections. We argue that Merz’s critique rests on a misunderstanding of our article, defend the daily life standard as a guardrail for leveraging cognitive biases, and argue that rejecting all behavioral influences is not a helpful nor a sustainable answer to their increasing use in trial recruitment.